정상인에서 시간 도메인과 스펙트럼 도메인 빛간섭단층촬영으로 측정한 황반두께 측정의 반복성 및 일치도 - 오세범; Se Beum Oh; 조원빈; Won Bin Cho; 문준웅; Jun Woong Moon; 김형찬; Hyung Chan Kim (Daihan angwa haghoi jabji, 2009)
목적: 정상인에서 time domain (TD) OCT와 spectral domain (SD) OCT로 황반두께를 측정해 그 반복성과 일치도를 비교해 보고자 하였다. 대상과 방법: 정상인 34안을 대상으로 TD OCT와 SD OCT로 3회 연속 황반두께와 총황반부피를 측정해 비교하였다. 개체 내 표준편차, 변동계수, 급내상관계수로 반복성을 알아보았고, Bland Altman plot으로 두 OCT의 일치도를 평가하였다. 또한 Pearson 상관계수 및 다중회기분석을 통해 두 OCT 사이의 상관관계에 대해서도 알아보았다. 결과: TD OCT와 SD OCT로 측정한 중심와두께, 총황반두께, 총황반부피의 개체 내 표준편차는 각각 11.53 ㎛/6.69 ㎛, 7.58 ㎛/2.55 ㎛, 0.48 mm3/0.09 mm3로 SD OCT에서 유의하게 낮았다. 변동계수와 급내상관계수는 TD OCT에서 각각 1.10~2.78%, 0.78~0.96%이었고, SD OCT에서 각각 0.29~0.94%, 0.92~0.99%이었다. 중심와두께, 총황반두께, 총황반부피의 95% 일치도 범위는 각각 67.94 ㎛, 29.01 ㎛, 0.98 mm3이었다. 두 OCT 사이의 모든 황반두께와 총황반부피는 통계적으로 유의한 상관관계를 보였다. 결론: 두 OCT 모두 황반두께 측정에서 높은 신뢰성을 보이나, SD OCT에서 더 높은 반복성을 보였다. 두 OCT로 측정한 황반두께는 측정기준의 차이 때문에 낮은 일치도를 보여 상호 교환적이지 못하나 유의한 상관관계를 보였다. <대한안과학회지 2009;50(5):710-716> Purpose: To compare the repeatability and agreement of macular thickness measurements using time domain (TD) optical coherence tomography (OCT) and spectral domain (SD) OCT in normal subjects. Methods: Thirty-four normal subjects were included. Three consecutive macular measurements were taken with TD OCT and SD OCT. Total and regional macular thickness and total macular volume obtained by the two OCTs were compared. Within-subject standard deviation (Sw), coefficient of variation (CVw), and the intraclass correlation coefficient (ICC) were calculated to evaluate repeatability. The agreement was examined with Bland Altman plots. The correlation was also evaluated with Pearson correlation coefficients and multiple regression analysis. Results: Sw for foveal thickness, total macular thickness, and total macular volume were 11.53 ㎛, 7.58 ㎛, and 0.48 mm3 for TD OCT and 6.69 ㎛, 2.55 ㎛, and 0.09 mm3 for SD OCT, respectively. The values for SD OCT were consistently lower, and this result was statistically significant. The range of the respective CVw and ICC values were 1.10~2.78% and 0.78~0.96% for TD OCT, and 0.29~0.94% and 0.92~0.99% for SD OCT, respectively. The SD OCT showed better repeatability for macular thickness measurements(all with p≤0.001). The spans of 95% limits of agreement for foveal thickness, total macular thickness, and total macular volume were 67.94 ㎛, 29.01 ㎛, and 0.98 mm3, respectively. The Pearson correlation coefficient of foveal thickness, total macular thickness, and total macular volume between the two OCT`s was statistically significant. Conclusions: Although both OCTs are reliable for macular thickness measurements, SD OCT shows better repeatability compared with TD OCT. Although macular thickness measurements obtained from the two OCTs can not be used interchangeably due to low agreement by different standards of measurement, there was a statistically significant correlation between the two OCT`s. J Korean Ophthalmol Soc 2009;50(5):710-716